A Disaggregate Freight Transport Model for Germany - Reiche, Sascha (Springer Fachmedien Wiesbaden : Vieweg, 2018)
Sascha Reiche develops a multi-modal commodity class specific freight model at the level of firms for the area of Germany that allows integration of macroscopic as well as disaggregate input data. Three modes of transport and 30 types of goods at the spatial level of 403 national and 29 international regions are considered, taking into account supply chain specifications of 88 different German business branches. The goal of this model is to provide fundamental insights into domestic freight transport organisations which should prove useful to decision makers with reference to the subject. Contents Freight Transport Modelling Framework for and Realisation of a Disaggregate German Freight Transport Model Modelling Freight Generation and Distribution Modelling of a Freight Network Combined Modal Split and Network Assignment Modelling Target Groups Lecturers and students of logistics, production, operations research, transport economics and spatial planning Authorities of politics, federal and municipal transport and spatial planners, traffic planners, logisticians, freight forwarders, shippers The Author Dr. Sascha Reiche currently works as research fellow at the Institute of Logistics and Material Handling Systems at Otto-von-Guericke University Magdeburg, Germany. His research focuses on empirical mobility research for freight and passenger transport, climate policy and technology-driven research on mobility innovation.